ISM AL-TAFḌĪL DALAM AL-QUR‘AN JUZ 11 SAMPAI 20 (ANALISIS MORFOSINTAKSIS): Comparative noun in Quran in JUZ 11 until 20 (Morphosintax Study) - Nafi', Syihabudin; Ahmad Miftahuddin; Hasan Busri (Universitas Negeri Semarang, 2024)
The comparative degree in the Arabic language is known by the term